Managing Waste Using the Integration of Lean and Ergonomic Methods - Mahdi, Naufal Abiyyu; Mahbubah, Nina (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2022)
CV. AAA is a company engaged in the production of water tanks. As a player in the manufacturing industry, CV. AAA performs continuous improvement in each production process to minimize losses due to non-value-added activities due to waste and ineffectiveness in carrying out the production process. This research objective evaluates activities that cause waste in the water tank production line with a Lean approach and ergonomics. This research begins by describing the current state map to identify waste throughout the production flow. Followed by the analysis of the occurrence of non-value-added activities at the stages of the production process. The results showed that three wastes were identified, namely Waiting, Defect, and Excess Processing. The non-optimal production process is because the tools used are manual labor which can lead to the risk of muscle injury to the operator. Nordic Body Map Scoring result obtained from four operators found that the final score is from medium to high level. Scenario improvement presented in future state map shows in reducing cycle time as well as lead time.